Service innovation and consumer welfare in the on- demand grocery retail market in South Africa - Makofane, Reabetswe (University of the Witwatersrand, Johannesburg, 2023)
To meet the need of time-constrained consumers in South Africa, last-mile logistics organisations and grocery retailers have implemented a grocery-on-demand solution, where consumers can order a basket of goods to be delivered to their home from within an hour to a day. This study locates the grocery-on-demand offering within innovation definitions and investigates the non-monetary value created by the actor network enacting the offering. In this study, a mixed-method approach was taken to understand the value created and enjoyed by firms and consumers. The understanding of value creation by firms is investigated through expert interviews and media analysis of the topic of grocery on demand, while consumer value- in-experience is investigated and estimated through a consumer survey. Six experts across retail and strategy consulting were interviewed, 30 articles were analysed and a sample of 420 consumers responded to the survey. The research findings are that firms are able to attain value through consumer-facing service innovations without charging high rates for the service. This is attained by enjoying the effects of improving their relationship with consumers. The research suggests that consumers enjoy more value through engaging this service innovation than they forfeit in payment, through time savings, increased well-being and improved relationships with the firms. This report contributes to models that business leaders and innovation managers can use to analyse potential value attainable through service innovation
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Innovation Studies to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Service innovation; Value-in-experience; Grocery on demand; Retail; Business-to-consumer market; Mixed-methods analysis; UCTD; SDG-8: Decent work and economic growth